Paleobiodiversity of the Tamengo and Guaicurus formations (Ediacaran-Cambrian boundary strata, Brazil): paleoecological, paleogeographic and biostratigraphic implications - ADÔRNO, Rodrigo Rodrigues (2024)
2024